Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The expression is:

[AB {C+(BD)'} + (AB)']CD

share|cite|improve this question

Using De Morgan's laws,

$[AB \{C+(BD)'\} + (AB)']CD=[AB \{C+B'+D'\} + A'+B']CD=[ABC+ABD' + A'+B']CD$

Now, $AE+A'=AE+A'(1+E)=A'+AE+A'E=A'+E(A+A')=A'+E$ $\implies ABC+A'=BC+A'$

$[ABC+ABD'+ A'+B']CD$


$=[A'+C+B'+ABD']CD $ (Using $AE+A'=A'+E$)


share|cite|improve this answer
Can you please define the 3rd last step of your answer...I could not really understand it. – Ali Feb 8 '13 at 15:28
@Ali. observe that $A'=A'\cdot U=A'(U+E)=A'U+A'E=A'+A'E$ where $U$ is the universal set. – lab bhattacharjee Feb 9 '13 at 15:14
Actually i am asking about the term (BC+B') how it comes....i still didn't understant.. – Ali Feb 9 '13 at 15:33
@Ali, $ABC+A'=ABC+A'(U+BC)=ABC+A'BC+A'=(A+A')BC+A'=BC+A',B'$ was already there which is paired with $BC$ to reach $C+B'$ using the same formula. – lab bhattacharjee Feb 9 '13 at 15:37

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.